A Comparative Study to Assess the Nutritional Status among School Age Children of Employed and Unemployed Mothers (A Study in Selected Schools of Nepalgunj, Banke, Nepal) - Vimala Sharma (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2023)
Nutrition is the science that studies the link between food and health, and is mainly focused on the role of nutrients in human growth, development, and maintenance. Healthy nutrition involves maintaining a nutritional condition that enables individuals to grow and maintain excellent health. The school age, which ranges from 6 to 12 years old, is a crucial period for physical growth and intellectual development in children. The socioeconomic status of families, social well-being, and health care system proficiency of communities, as well as the environmental impact, are important factors that affect child health. Viewing malnutrition as an issue in human ecology provides a range of approaches for prevention. The objective of this study was to evaluate the nutritional status of school-age children whose mothers were employed or unemployed and attending selected schools in Nepalgunj, Banke. A descriptive comparative research design was employed for the study, and stratified random sampling was used to select 120 students from Nepalgunj, Banke. Data were collected using a self-developed structured questionnaire. The study results showed that children with underweight (51.6%) were more prevalent among employed mothers' children than unemployed mothers' children (20%). However, children with normal weight (43.3%) were more prevalent among children of unemployed mothers than employed mothers (25%). An association was found between school type and maternal employment status with children's body mass index (BMI), and the P-values were <0.001 and <0.02, respectively. The nutritional status of children is a crucial factor for their growth and development. This study indicated that underweight was more prevalent among children of employed mothers, and children of unemployed mothers had a normal weight. Maternal employment status and school types, such as public and private schools, were associated with children's BMI. These factors should be considered while designing interventions to enhance children's nutritional status.